Needs analysis on the development of stimulation setting using CTML model in the subject of drawing studies / Mohd Khairul Azlan Rahmat and Siti Zuraida Maaruf - Rahmat, Mohd Khairul Azlan; Maaruf, Siti Zuraida (Penerbit UiTM (UiTM Press), 2017)
The aim of this research is to identify the possibility of developing the Stimulation Room Courseware for Drawing Studies method in additional to and substitute for outdoor learning and indoor learning in the teaching and learning of Drawing Studies for tertiary level Art Education in Malaysia. This courseware and method could be integrated with ICT to enhance the teaching and learning in Visual Art Education. This research was conducted by utilizing the Design Developmental Research that consisted of three phases but the present paper discusses only the needs analysis that was carried out during the 1st phase with the objective of determining Art Educators' perspectives of applying the Stimulation Room Courseware for Drawing Studies in their courses.